Characterization of R132H mutation-specific IDH1 antibody binding in brain tumors - Capper, David; Weißert, Susanne; Balß, Jörg; Habel, Antje; Meyer, Jochen; Jäger, Diana; Ackermann, Ulrike; Tessmer, Claudia; Korshunov, Andrey; Zentgraf, Hanswalter; Hartmann, Christian; Deimling, Andreas von (Brain pathology, 2010)
Heterozygous point mutations of isocitrate dehydrogenase (IDH)1 codon 132 are frequent in grade II and III gliomas. Recently, we reported an antibody specific for the IDH1R132H mutation. Here we investigate the capability of this antibody to differentiate wild type and mutated IDH1 protein in central nervous system (CNS) tumors by Western blot and immunohistochemistry. Results of protein analysis are correlated to sequencing data. In Western blot, anti-IDH1R132H mouse monoclonal antibody mIDH1R132H detected a specific band only in mutated tumors. Immunohistochemistry of 345 primary brain tumors demonstrated a strong cytoplasmic and weaker nuclear staining in 122 cases. Correlation with direct sequencing of 186 cases resulted in consensus of 177 cases. Genetic retesting of cases with conflicting findings resulted in a match of 186/186 cases, with all discrepancies resolving in favor of immunohistochemistry. Intriguing is the ability of mIDH1R132H to detect single infiltrating tumor cells. The very high frequency and the distribution of this mutation among specific brain tumor entities allow the highly sensitive and specific discrimination of various tumors by immunohistochemistry, such as anaplastic astrocytoma from primary glioblastoma or diffuse astrocytoma World Health Organization (WHO) grade II from pilocytic astrocytoma or ependymoma. Noteworthy is the discrimination of the infiltrating edge of tumors with IDH1 mutation from reactive gliosis.